Interior design and construction project management: performance and productivity in Malaysian building industry - Jasmani, Ismail (IIUM Press, 2016)
The practice of Interior Design (ID), Architecture, Mechanical & Electrical and Facilities component drawings such as conceptual design and construction drawings would need to be integrated and coordinated between the consultants and the contractor drawings. All related drawings are required to be resolved and agreed upon, so as not to cause obstacles at the actual construction site and to improve the business performance in terms of time and cost of the project. A further review of the performance measured in the interior design construction industry also indicates that productivity is an inadequate measure for identifying improvement targets and control activities.The use of a more holistic set of measures is recommended in order to ensure more relevant and timely information. The purpose of this study is to explore the integration and coordination of the respective consultants’ involvement in the project construction management that will help clients on timing and costing of the projects. The lack of coordination between multidisciplinary scope of work within project construction managements in interior, architecture, and other related fields will increase time and cost of the ID Construction projects (IIDA Report, 1998).